2003
DOI: 10.1111/j.1151-2916.2003.tb03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Silicon Carbide and Silicon Carbide–Graphite Composite Ceramics in Sliding Contact

Abstract: A monolithic SiC ceramic and two SiC–C composite ceramics containing 10 and 20 vol% graphite were fully densified with Al4C3 and B4C as additives. The tribological properties of these materials were evaluated by sliding against sintered silicon carbide under dry conditions using two tribometers, block‐on‐ring and pin‐on‐disk, where wear occurred under low and high contact stresses, respectively. For all three materials, under low stress, worn surfaces were smooth and wear processes were dominated by tribochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Actually, energy dispersive X-ray spectroscopy analyses on the worn surfaces of these block specimens could always detect an oxygen peak in the spectra, just as those shown in our previous paper. 10 Due to the lack of pull-out and fracture of carbon fibers, an expected lubricious layer containing graphite phase on the contacting interface was not formed, and therefore the friction coefficients of the SiCC composites could not be lowered.…”
Section: Results and Discussion 31 Mechanical Propertiesmentioning
confidence: 99%
“…Actually, energy dispersive X-ray spectroscopy analyses on the worn surfaces of these block specimens could always detect an oxygen peak in the spectra, just as those shown in our previous paper. 10 Due to the lack of pull-out and fracture of carbon fibers, an expected lubricious layer containing graphite phase on the contacting interface was not formed, and therefore the friction coefficients of the SiCC composites could not be lowered.…”
Section: Results and Discussion 31 Mechanical Propertiesmentioning
confidence: 99%
“…Tribological properties depend upon the microstructure and properties of the preform [8,51]. The effect of graphitization on microstructure and mechanical properties of C/C-SiC composites is investigated by many researchers, but its effect on tribological properties of C/C-SiC composites has not been investigated much [52][53][54][55][56]. Figure 12 shows the curves of coefficient of friction of samples ((a) without graphitization and (b) with graphitization) as a function of braking time.…”
Section: Effect Of Graphitization Of C/c Preform On Tribological Prmentioning
confidence: 99%
“…This results in increase in coefficient of friction. However, graphite has a good solid lubricant property because it has weakly bonded layer structure [53,56]. This lubricating property helps to avoid the initial high peak in coefficient of friction and moderate the fluctuation in coefficient of friction in the latter stage.…”
Section: Effect Of Graphitization Of C/c Preform On Tribological Prmentioning
confidence: 99%
“…A few previous studies showed that the graphite phase in SiC/graphite composites could often exert a solid lubricating effect, leading to lower friction coefficients of the SiC/graphite composites than that of a monolithic SiC. [3][4][5][6] For example, it was found in our recent study that adding 20 vol% graphite into SiC could make the friction coefficient decrease from 0.63 to 0.45. 6 Apart from graphite, carbon materials exist in a variety of other forms.…”
Section: Introductionmentioning
confidence: 97%